Attractiveness Ratings for Musicians and Non-musicians: An Evolutionary-Psychology Perspective - Bongard, Stephan; Schulz, Ilka; Studenroth, Karin U.; Frankenberg, Emily (Frontiers in Psychology, 2019)
From an evolutionary perspective, musical behavior such as playing an instrument can be considered as part of an individual’s courting behavior. Playing a musical instrument or singing might fulfill a function similar to that of a bird’s colored feathers: attracting attention. Therefore, musicians may be rated as more attractive than non-musicians. In an online survey, 137 volunteers (95 female) with ages ranging from 16 to 39 years rated the attractiveness of fictitious persons of the opposite sex described in short verbal profiles. These profiles differed with respect to whether the described person made music or not. Additionally, the musicians’ profiles varied with regard to whether the described person played music in public or in private only. Results show that musicians’ profiles were not generally rated as more attractive than non-musicians’, but attractiveness did vary according to setting: private musicians were rated as most attractive, followed by non-musicians and public musicians. Furthermore, results indicate that participants who played a musical instrument themselves gave higher ratings to profiles of musicians. But for participants who do not make music themselves, higher attractiveness ratings for musicians playing instruments in private settings was found. These results indicate that the impression of sharing a common interest (making music) and furthermore making music in private instrumental settings seems to make people attractive to other people.